Nanoporous metal organic frameworks as hybrid polymer–metal composites for drug delivery and biomedical applications. Issue 4 (April 2017) - Beg, Sarwar; Rahman, Mahfoozur; Jain, Atul; Saini, Sumant; Midoux, Patrick; Pichon, Chantal; Ahmad, Farhan Jalees; Akhter, Sohail
Graphical abstract: Metal organic frameworks (MOFs), a hybrid polymer–metal composite for drug delivery and other biomedical applications. Highlights: Metal organic frameworks (MOFs) are nanoporous hybrid polymer–metal composites of unique structures, tunable pore size and volume. MOFs possess excellent material characteristics for diverse biomedical applications including drug delivery, imaging and theranostics. Surface functionalization is easy with MOFs for specific targeting. Drug molecules can be directly loaded as linkers with the possibility of a therapeutic metal as the inorganic component of the MOFs. Acceptable degradability and minimal or no toxicity have been reported for MOFs in preclinical studies. Abstract : Metal organic frameworks (MOFs), porous hybrid polymer–metal composites at the nanoscale, are recent innovations in the field of chemistry; they are novel polymeric materials with diverse biomedical applications. MOFs are nanoporous materials, consisting of metal ions linked together by organic bridging ligands. The unique physical and chemical characteristics of MOFs have attracted wider attention from the scientific community, exploring their utility in the field of material science, biology, nanotechnology and drug delivery. The practical feasibility of MOFs is possible owing to their abilities for biodegradability, excellent porosity, high loading capacity, ease of surface modification, among others. In this regard, this review provides an account of various types of MOFs, their physiochemical characteristics and use in diverse disciplines of biomedical sciences – with special emphasis on drug delivery and theranostics. Moreover, this review also highlights the stability and toxicity issues of MOFs, along with their market potential for biomedical applications. Abstract : Metal organic frameworks as hybrid nanocomposites in drug delivery and biomedical applications.